PALEOGEOGRAPHIC STATE OF THE EASTERN ISLET REGION, STAGES OF ASSIMILATION (TAMADDUN NURI JURNALI, 2024)
It is known from archeological sources that the foothills of the Sultan Uwais mountain, which is the geological base of the Eastern Archipelago in the west, were inhabited by hunters of the Stone Age, the Late Stone Age, (Burli-3) Mesolithic, and the Early Neolithic. The article analyzes the political history of the Eastern Aral Bay region based on written sources and archaeological research.